Menstrual Disorders Condition of Patients Treated at UIN Sunan Ampel’s Primary Clinic - Dwi Rukma Santi; Eko Teguh Pribadi (State Islamic University of Sunan Ampel, 2018)
Around seventy-five percent of the women on stage final teenagers experiencing disruptions associated with menstruation. Based on Clinical UINSA annual report of the period 2015 - 2017 shows that the number of cases of patients with menstrual disorders to increased. The onset of menstrual disorders will cause pain physically as well as lowering the learning capabilities of the student. The objectif of this study is to describe the conditions of menstrual disorders in patients treated at Clinic Primary UIN Sunan Ampel Surabaya. This was a descriptive research with materials taken from secondary data obtained from the medical record of patients who menstrual disorders during the period 2015 - 2017. The results showed that patients who menstrual disorders as many as 192 people. Characteristics that are experiencing menstrual disorders based on age at most in the age group 18 - 19 years old (45.32%), based on the age of menarche group 10 - 11 years old (62.50%), weight loss most (63%) are 46 – 55 kg, level semester part (44.30%) in semester 1 - 2. While the majority of cycle disorders (48.53%) is oligomenorea, long menstrual disorders is hipermenorea/menorhagia (64.52%) and other disorders are the most prevalent is dysmenorrhoea (68.05%).Needed for increased knowledge about various types of menstrual disorders so that the young women were able to recognize about reproductive health and preventive care.